Natural killer cells induce HIV-1 latency reversal after treatment with pan-caspase inhibitors - Furtado Milão, Joana; Love, Luca; Gourgi, George; Derhaschnig, Lukas; Svensson, J. Peter; Sönnerborg, Anders; van Domselaar, Robert (Frontiers in Immunology, 2022)
The establishment of a latency reservoir is the major obstacle for a cure of HIV-1. The shock-and-kill strategy aims to reactivate HIV-1 replication in HIV -1 latently infected cells, exposing the HIV-1-infected cells to cytotoxic lymphocytes. However, none of the latency reversal agents (LRAs) tested so far have shown the desired effect in people living with HIV-1. We observed that NK cells stimulated with a pan-caspase inhibitor induced latency reversal in co-cultures with HIV-1 latently infected cells. Synergy in HIV-1 reactivation was observed with LRAs prostratin and JQ1. The supernatants of the pan-caspase inhibitor-treated NK cells activated the HIV-1 LTR promoter, indicating that a secreted factor by NK cells was responsible for the HIV-1 reactivation. Assessing changes in the secreted cytokine profile of pan-caspase inhibitor-treated NK cells revealed increased levels of the HIV-1 suppressor chemokines MIP1α (CCL3), MIP1β (CCL4) and RANTES (CCL5). However, these cytokines individually or together did not induce LTR promoter activation, suggesting that CCL3-5 were not responsible for the observed HIV-1 reactivation. The cytokine profile did indicate that pan-caspase inhibitors induce NK cell activation. Altogether, our approach might be–in combination with other shock-and-kill strategies or LRAs–a strategy for reducing viral latency reservoirs and a step forward towards eradication of functionally active HIV-1 in infected individuals.